Yb/Er coordinatively doping in bilayer WSe2 for fascinating up-conversion luminescence. (December 2020) - Wang, Caiyun; Xu, Lingyi; Jin, Haonan; Li, Chen; Zhang, Zhi; Li, Luying; Chen, Yibo; Su, Jun; Liu, Nishuang; Lai, Jianjun; Long, Fei; Jiang, Xueliang; et al.
Abstract: Benefited from the controllable synthesis of large-scale transition metal dichalcogenides (TMDCs), abundant physical properties of TMDC van der waals heterostructures, such as moire-exciton, electrostatic gating effects, interlayer magnetism, are widely reported. In optoelectronic categories, the applications of TMDC van der waals heterostructures involve interlayer exciton lasers, single photon emitters, and light-emitting diodes (LEDs). However, the employment of TMDCs in visible light emitter is still challenging due to their narrow band gap. The up-converted luminescence from TMDCs could be an effective way to achieve this goal, which has been reported rarely. In this work, the rare earth Yb/Er co-doped bilayer WSe2 of atomic thickness is designed and synthesized using precursor ultrasonic mixing and molten-salt assisted chemical vapor deposition technology. A fascinating up-converted luminescence has been realized on the Yb–Er co-doped bilayer WSe2 excited by 980 nm laser. The up-conversion luminescence peak at 550 nm originates from Er 3+ energy level transition 4 S3/2 → 4 I15/2 . Furthermore, a modulated visible electroluminescence is probed from the LED with architecture of Cr/Au electrodes on Yb–Er co-doped bilayer WSe2 /monolayer MoSe2 van der waals heterostructure. Unveiling up-conversion luminescence in TMDCs opens a novel way of utility in photomedicine, infrared thermometer, and infrared photography, etc . Graphical abstract: Image 1 Highlights: The rare-earth Yb-Er co-doped bilayer WSe2 with atomical thickness is designed and synthesized. When the temperature climbs from 88 K to 573 K, band gap of Yb/Er co-doped bilayer WSe2 decreases from 1.63 eV to 1.38 eV. The up-conversion luminescence peaks at 550 nm, 610 nm are detected on Yb-Er co-doped bilayer WSe2 excited by 980 nm laser.